Effect of gas flow rate on welding of ferritic stainless steel using alternative electrode 308L for railway coal wagons - Maleka, Audrey (My University, 2022)
In this study 3Cr12 stainless steel was welded using 308L as an alternative consumable electrode using Gas Metal Arc Welding (GMAW) process. The electrode was selected because it is relatively cheap compared to the currently used 309L electrode. The aim of the study was to investigate the effect of varying shielding gas (helium) flow rate (10L/min, 15L/min, 20L/min, and 25L/min) on the quality of the weld, microstructural, mechanical and corrosion properties. Magnetic particle inspection fluorescent testing is the non-destructive test that was performed to evaluate the soundness of the welds. Subsequent tests were performed on defect free samples. Surface properties and morphologies of the samples were analysed by stereoscope, optical microscope and scanning electron microscope (SEM). Phases were characterised by X-ray diffraction (XRD). Mechanical tests were evaluated by conducting hardness, tensile and Charpy V-notch tests. Huey corrosion test was used to study the corrosion behaviour of the welded samples in a boiling solution of 65% HNO3 for 48 hours. The microstructural results showed that the parent metal had a fully ferritic structure, while the HAZ contained coarse grained ferrite with intergranular martensite. The weld consisted of austenite, ferrite, and martensite, obtained phases were further confirmed by XRD.As the gas flowrate was increasing it was observed that the martensite content increased on the heat affected zone and the weld leading to increased hardness and ultimate tensile strength however reducing the % elongation. In addition, all flowrate managed to exceed the absorbed energy expected for the material. No intergranular corrosion (sensitization) was observed on any of the samples on both Huey corrosion test and electro-etching.
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Science in Engineering to the Faculty of Engineering and Built Environment, School of Chemical and Metallurgical Engineering, University of the Witwatersrand, Johannesburg, 2022